A luminescent zinc(ii) coordination polymer with unusual (3, 4, 4)-coordinated self-catenated 3D network for selective detection of nitroaromatics and ferric and chromate ions: a versatile luminescent sensor. Issue 17 (19th April 2018) - Zhang, Ya-Qian; Blatov, Vladislav A.; Zheng, Tian-Rui; Yang, Chang-Hao; Qian, Lin-Lu; Li, Ke; Li, Bao-Long; Wu, Bing
Abstract : A zinc coordination polymer is a sensor for detection of TNP, Fe 3+, Cr2 O7 2− and CrO4 2− . Abstract : A zinc(ii ) coordination polymer [Zn3 (mtrb)3 (btc)2 ]·3H2 O n (1 ) was synthesized and characterized (mtrb = 1, 3-bis(1, 2, 4-triazole-4-ylmethyl)benzene, btc = 1, 3, 5-benzenetricarboxylate). The polymer1 shows an unusual (3, 4, 4)-coordinated self-catenated 3D network with the point symbol of 6 3 2 6 2 ·8 2 ·10 2 6 4 ·8 2 2 . The polymer1 is the first luminescent sensor for the detection of 2-amino-4-nitrophenol (ANP). The polymer1 is also a good luminescence sensor for detection of TNP, 2, 4-DNP, 4-NP, ANP and 2-NP in MeOH, particularly for TNP. The order of detection efficiency is TNP > 2, 4-DNP > 4-NP > ANP > 2-NP. The polymer1 also exhibits high sensitivity and selectivity as a luminescence sensor for the detection of Fe 3+, Cr2 O7 2− and CrO4 2− in aqueous solution. Our experiments showed that the presence of interfering ions had no significant effect on the sensing of Fe 3+, Cr2 O7 2− or CrO4 2− ions. The detection limits for TNP, ANP, Fe 3+, Cr2 O7 2− and CrO4 2− are 0.22 μM, 4.12 μM, 1.78 μM, 2.83 μM, and 4.52 μM, respectively. The luminescence sensor is stable and can be recycled for detection at least five times. The possible quenching mechanisms are discussed. The polymer1 is also an effective photocatalyst for degradation of methylene blue (MB) under visible or UV light irradiation.